Manajemen PERTALITE (Permainan Tradisional Berbasis Literasi) Tumbuhkan Generasi Rahmatan Lil Alamin - Lastri Khasanah; Suratiyah; Vivit Andianingsih; Nur Qonita Khamidah (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to describe the implementation of the Manajemen PERTALITE program (Traditional Game-Based Literacy to Foster Rahmatan Lil ‘Alamin Generation) through modified traditional games at RA Masithoh Bantar and to identify its benefits for early childhood development. This study employed a qualitative descriptive approach involving teachers and Group B students of RA Masithoh Bantar as research subjects. Data were collected through observation, interviews, and documentation. Data analysis used the Miles and Huberman model consisting of data reduction, data display, and conclusion drawing. The results showed that modified traditional games such as marbles, congklak, and sundamanda improved children’s early numeracy literacy, fine motor skills, gross motor skills, social-emotional abilities, communication skills, and Islamic character development. Traditional game-based learning also created an active, enjoyable, and meaningful learning atmosphere for early childhood learners. Furthermore, this program served as a form of local cultural preservation integrated with Islamic character education and numeracy literacy. Therefore, modified traditional games can be used as an innovative learning strategy in early childhood education.